Optical properties of circular photonic crystal fibers filled with carbon tetrachloride - Duc, Hoang Trong; Bao Tran, Le Tran; Thao, Tran Ngoc; Lanh, Chu Van; Thuy, Nguyen Thi (Vietnam Journal of Science and Technology, 2023)
In this work, the dispersion properties and nonlinear properties of circular photonic crystal fibers were improved by a combination of carbon tetrachloride infiltration into the core and modification of the air hole diameters d1 and d2 of rings in the cladding. The quantities such as dispersion, effective mode area, nonlinear coefficient, and low confinement are analyzed in detail. Based on the survey results, two photonic crystal fibers with optimal optical properties were proposed which are beneficial for supercontinuum generation. The first fiber with Ʌ = 1.0 µm, d1/Ʌ = 0.6, has an all-normal dispersion of –10.785 ps/nm.km at a pump wavelength of 0.985 µm. The high nonlinear coefficient of 581.795 W–1.km–1 and the low confinement loss of 3.904 dB/m are also achieved with this fiber. SC broadband under the influence of soliton is expected to be generated when using the second fiber (Ʌ = 2.0 µm, d1/Ʌ = 0.3) with flat and low anomalous dispersion at the pump wavelength of 1.3 µm.